Bookkeeping essentials : how to succeed as a bookkeeper - Bragg, Steven M. (Hoboken, N.J. : Wiley, 2011)
'The Vest Pocket Bookkeeper will include dozens of best practices that give bookkeepers insights into how to be more efficient and effective in their jobs. The book also reveals the key controls needed to reduce the risk of fraud. The book covers virtually all areas of importance that a bookkeeper must be aware of--topics to be covered are: Cash and accrual accounting, Purchasing and payables, Billing and collections, Income taxes, Cash receipts, Petty cash, Bank reconciliations, The financial statements, Closing the books. Financial statement analysis. Financial reports. Record archiving. Auditing.'--Provided by publisher.
Includes index.
Keywords: Bookkeeping; Accounting; Fraud -- Prevention